Berlin, Deutschland. Fernpraktika am DAI – ein neues Format zur Nachwuchsförderung. Die Fernpraktika des Jahres 2020 und der ersten Jahreshälfte von 2021 - Sielhorst, Barbara (e-Forschungsberichte des DAI, 2021)
At the beginning of the pandemic in spring 2020 the DAI relaunched a new format of online internships which established itself as an effective instrument for the development of junior researchers. Despite the possibility to complete an often required internship from the student’s point of view the format offers also the chance to get a deeper look inside current research of the DAI and thus getting important inspirations and contacts for their future career. In turn for the researchers at the DAI the internships offer the possibility to present their projects in progress, to discuss current research issues with the students and to gather experience in digital teaching.